INVESTIGATION OF THE KINETICS OF THE MIXING PROCESS AT VARIABLE SPREADS HEAT SUPPLY - A. N. Ostrikov (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2015)
The investigation of the kinetics of mixing creamy vegetable spreads with a variable heat supply. The time of each of the periods of re-mixing. Stirring at a temperature of 65 °C optimum convective mixing period was 2.5 minutes. Convective mixing duration after the beginning of crystallization of the product (i.e., by stirring at a temperature of 30 ... 15 ° C) was 5 minutes. The second period at a temperature of 65 ° C was 2.2 min. Mixing diffusion time during 9 minutes to crystallize the product. The entire mixing process was conditionally divided into three temperature-time periods: 1 a period of intense agitation; 2 during product cooling to a crystallization temperature; 3 the product during crystallization. The investigations of the process at different speeds working body were to choose the best, to get good distribution of all components in the minimum time. The result was that the spread manufactured according to the proposed formulation meets the optimal mixing time stirrer speed is 150 rev / min (during intensive stirring), 10 rev / min (during cooling of the product to a crystallization temperature) and 15 rev / min during crystallization. The optimal mixing time using the dependence of the dimensionless concentration of a key component of the mixing time. The result was the optimum time for process spread 4.7 min at 65 ° C. Conducted research to determine the optimal mixing time in the crystallization of the product, it was 14 minutes. The increase in the mixing time required for uniform distribution of components in the mixture in small quantities.